On Caputo–Riemann–Liouville Type Fractional Integro-Differential Equations with Multi-Point Sub-Strip Boundary Conditions - Ahmed Alsaedi; Amjad F. Albideewi; Sotiris K. Ntouyas; Bashir Ahmad (Mathematics, 2020)
In this paper, we derive existence and uniqueness results for a nonlinear Caputo–Riemann–Liouville type fractional integro-differential boundary value problem with multi-point sub-strip boundary conditions, via Banach and Krasnosel’ski<semantics><mover accent="true">i⏝</mover></semantics>’s fixed point theorems. Examples are included for the illustration of the obtained results.